Pandangan Tokoh Masyarakat NU dan Muhammadiyah Terhadap Perempuan Bekerja Mencari Nafkah Keluarga (Studi Kasus di Desa Tembok Kidul) - Suci Alifia, Asyiva (Al-Hukkam: Journal of Islamic Family Law, 2022)
The problem raised in this study is to explore and analyze the views of NU and Muhammadiyah community leaders towards women who work to earn a living for their families. This research uses the type of field research. The approach used is a qualitative approach. The data sources are primary and secondary data sources. Data collection techniques are observation, interviews, documentation and triangulation. Data analysis in this study used interactive analysis techniques. The results showed that the weakness of a husband in earning a living can be overcome by the wife's willingness to help her husband's work and the results of this study suggest that there is no prohibition for women to continue working as desired on condition that their position as wife and mother in the household is not forgotten, because the mother is the first school for their generations, this opinion is based on the Qur'an and hadith in accordance with the times, although there are those who are not allowed to work because they see that women who are busy outside have more harm than those who stay at home, but all can resolved if there is harmonious communication.